Process Variables Optimisation of Polypropylene Based Fibre-Metal Laminates Forming using Finite Element Analysis - Sivakumar, Dhar Malingam (Trans Tech Publications, Switzerland, 2009)
This study investigates the effect of preheat temperature, blank holder force and feed rate on the formability of polypropylene based Fibre-Metal Laminates. Finite element method combined with Design of Experiments was used to determine the influence of the forming process parameters. The design of experiments was used to identify the relative influence of each process parameter considered in this study. A reduced set of coupled structural-thermal simulations using Ls-Dyna were carried out using a L9 orthogonal array. Simulations were carried out on the forming of domes. It was found that the blank holder force has the greatest influence to increase the minor/major ratios followed by feed rate and pre heat temperature. A more thorough investigation of preheat temperature illustrated an optimum preheat temperature at 130 °C.